A far-red fluorescent probe based on a phospha-fluorescein scaffold for cytosolic calcium imaging. Issue 3 (14th December 2017) - Ogasawara, Hiroaki; Grzybowski, Marek; Hosokawa, Riho; Sato, Yoshikatsu; Taki, Masayasu; Yamaguchi, Shigehiro
Abstract : A far-red fluorescent probe based on a phospha-fluorescein scaffold enables the visualization of cytosolic Ca 2+ dynamics in living cells. Abstract : The far-red emissive fluorescent probe CaPF-1 based on a phospha-fluorescein scaffold enables the detection of cytosolic calcium ions in living cells. The probe can be excited in the red region ( λ abs = 636 nm) and exhibits a sufficiently high fluorescence turn-on response in the far-red region ( λ em = 663 nm) upon complexation with calcium ions. The hydrophilic and anionic characteristics of this phospha-fluorescein fluorophore allowed the cytosolic localization of CaPF-1. Moreover, it was possible to visualize histamine-induced calcium oscillation in HeLa cells using CaPF-1.